Recommending prolonged bedaquiline use for the treatment of highly resistant strains of tuberculosis. Issue 5 (9th November 2017) - Furin, Jennifer; Lessem, Erica; Cox, Vivian
We read with interest the article by Caminero et al. [1] proposing a standardised approach to treating both pre-extensively drug-resistant tuberculosis (pre-XDR-TB) and extensively drug-resistant tuberculosis (XDR-TB). This proposal is welcome considering the dearth of evidence-based recommendations on the optimal management of highly resistant tuberculosis (TB) [2]. Given the increasing recognition of the prevalence, morbidity and mortality associated with pre-XDR and XDR-TB, as well as the significant improvement in treatment outcomes with the use of novel and repurposed drugs [3], a clear policy for optimal management of these forms of TB is urgently needed. Treatment of XDR-TB by prolonged use of bedaquiline is appropriate for some individuals http://ow.ly/VmpN30fzReK